Web-Based Prototype Integrating Islamic Ethical Communication in E-Commerce - Ria Rosalina; Bambang Judi Bagiono (PT. Student Rihlah Indonesia, 2026)
This study designs a web-based prototype that integrates Islamic ethical communication principles qoulan sadida, qoulan layyina, tabligh, ‘adl (justice), and amanah—into buying and selling activities at ABCD Store, Jakarta. In the context of rapid digitalization and increasingly competitive retail markets, ethical challenges such as misleading information, unfair pricing, weak transparency, and limited accountability often undermine consumer trust. To address these issues, this research introduces a Conscious-Based Method, which embeds ethical validation mechanisms directly into transactional processes. The Conscious-Based Method operates through four structured stages. The findings demonstrate that embedding computational ethical controls within a web-based retail system significantly enhances accountability, fairness, and sustainable consumer trust. This study contributes to the development of ethically embedded digital commerce architectures by operationalizing Islamic ethical communication principles into measurable system indicators. Practically, the proposed prototype provides a scalable governance model that can be adopted by small and medium-sized enterprises to strengthen consumer trust and reduce transactional disputes in digital retail environments.